THE INFLUENCE OF SOCIAL MEDIA, RISK PERCEPTION, AND HERDING ON STUDENT INVESTMENT DECISIONS - Evelyna Charisia Darianto; Gusti Ayu Putu Eka Dewi Prihantari (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Investment growth in Indonesia's capital market has shown a significant increase, as reflected in the rising number of investors registered with PT Kustodian Sentral Efek Indonesia (KSEI), especially among the youth under 30 years of age. This study aims to analyze the influence of social media, risk perception, and herding behavior on student investment decisions. The subjects of this study were undergraduate students of the Accounting Study Program, Faculty of Economics and Business, Udayana University, class of 2021. The sample was determined using purposive sampling, resulting in 180 respondents. Data were analyzed using multiple linear regression analysis. The findings reveal that social media, risk perception, and herding behavior all have a positive influence on students' investment decisions. These findings offer empirical support for behavioral finance theory and the theory of planned behavior in understanding factors that influence student investment behavior.